Removal of Dibutyl Phthalate and Its Effects on Bacterial Communities in Lab-scale Constructed Wetlands - Wang, Xiaohui; Yang, Jingdan; Du, Shuai; Yuan, Yuan; Zhu, Minghan; Li, Yuan; Zhu, Xiaobiao (Journal of Environmental Accounting and Management, 2026)
The environmental release of phthalate acid esters (PAEs), and their potential health and environmental risks have attracted increasing concerns. The removal efficiencies of the most frequently identified PAE, dibutyl phthalate (DBP), and their effects on bacterial community structures were examined in two vertical flow constructed wetlands (VFCWs). In this study, the influent DBP concentration was about 600 μg/L and the removal rates reached above 61.1% during the study period. Catalase activity analysis showed that both treatment and control systems had significantly higher enzyme activities in the surface soil than subsurface substrate, and DBP significantly deteriorated the catalase activities (p < 0.05). Miseq sequencing data showed that DBP significantly increased the diversity of bacterial community (p < 0.05) and altered the overall bacterial community structure in wetland systems as revealed by Principal component analysis (PCA). The relative abundance of five genera, including Azohydromonas, Bdellovibrio, Desulfobulus, Roseomonas and Thiobacillus significantly decreased in the wetland at the present of DBP. However, four genera Propioniciclava, Geobacter, Paludibacter and Bacillus significantly increased under DBP. This study provides insights into our understanding the treatment performance of DBP in wetland systems, and their effects on the diversity and structure of bacterial communities under DBP in wetland systems.